Actin-dependent plastid movement is required for motive force generation in directional nuclear movement in plants - Higa, Takeshi (National Academy of Sciences, 2014)
Nuclear movement and positioning are indispensable for most cellular functions. In plants, strong light-induced chloroplast movement to the side walls of the cell is essential for minimizing damage from strong visible light. Strong light-induced nuclear movement to the side walls also has been suggested to play an important role in minimizing damage from strong UV light. Although both movements are regulated by the same photoreceptor, phototropin, the precise cytoskeleton-based force generation mechanism for nuclear movement is unknown, in contrast to the short actin-based mechanism of chloroplast movement. Here we show that actin-dependent movement of plastids attached to the nucleus is essential for light-induced nuclear movement in the Arabidopsis leaf epidermal cell. We found that nuclei are always associated with some plastids, and that light-induced nuclear movement is correlated with the dynamics of short actin filaments associated with plastids. Indeed, nuclei without plastid attachments do not exhibit blue light-induced directional movement. Our results demonstrate that nuclei are incapable of autonomously moving in response to light, whereas attached plastids carry nuclei via the short actin filament-based movement. Thus, the close association between nuclei and plastids is essential for their cooperative movements and functions.